Students’ Clubs Ranking System / Nurdiana Mohd Jaswary - Mohd Jaswary, Nurdiana (2017)
The Students’ Clubs Ranking System is a web-based system based on the case study and will be implemented and use by the Unit Kualiti Mahasiswa member, admin, and TR HEP. As for the current process, Microsoft Excel are used to rank the club and the paper-based form also are used to tick on which criteria does each of the activity information belongs to. To solve the problem of the current process, Rapid Application Development (RAD) model is followed which consists of four phases which are requirements planning phase, user design phase, construction phase and lastly cutover phase. Besides, to identify whether the functionality and usability of the system goes well, the system testing and evaluation from experts and users are conducted. The evaluation involved three experts and 30 respondents as a user. As a result from the user evaluation, the highest mean is 4.10 with the standard deviation of 0.55, based on satisfaction for the user evaluation. The recommendation for future work is to cater for the three campuses of UiTM Cawangan Terengganu.